Teaching practical topics to nursing students at clinical skills centres: A total mapping of Swedish universities. (June 2021) - Axelsson, Malin Tiger; Årestedt, Liselott; Swahnberg, Katarina; Oscarsson, Marie
Teaching practical topics is a central part of nursing education. The aim of this study was to describe the teaching of practical topics to nursing students at clinical skills centres (CSCs) in Sweden regarding organisation, structure and content. Data collection consisted of structured and open-ended questions through telephone interviews with responsible educators at all Swedish Universities ( n  = 25). The analyses consisted of descriptive statistics and compilation. The results showed that teaching of practical topics varied, depending on each university's pre-requisites, and a lot of resources were needed. Teaching at CSCs enabled integration of practical and theoretical knowledge. Having large student groups and confusion over terms hamper the teaching, and there was lack of a specific education for the educators at CSCs. Teaching practical topics at CSCs is a complex task, and educators need competences in nursing, theoretical knowledge and pedagogy.